Klinefelter syndrome with low gonadotropin levels. (29th December 2015) - Cherian, Kripa Elizabeth; Jebasingh, Felix K; Kapoor, Nitin; Paul, Thomas Vizhalil
Abstract : Klinefelter syndrome is usually characterised by the presence of a eunuchoid body habitus and testes that are usually small and firm, with low testosterone, and elevated luteinising hormone and follicle-stimulating hormone levels, consistent with hypergonadotropic hypogonadism. Low levels of gonadotropins in karyotypically proven cases are not expected, they are extremely rare occurrences. We report a case of a patient who was diagnosed to have Klinefelter syndrome (47 XXY) with low gonadotropin levels. The rest of his anterior pituitary hormonal profile was normal with no lesions in the pituitary gland on imaging. He was continued on androgen replacement therapy.